2012
DOI: 10.4085/1062-6050-47.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress and Cardiovascular, Hormonal, and Heat Shock Proteins in Humans

Abstract: Context: Conditions such as osteoarthritis, obesity, and spinal cord injury limit the ability of patients to exercise, preventing them from experiencing many well-documented physiologic stressors. Recent evidence indicates that some of these stressors might derive from exercise-induced body temperature increases.Objective: To determine whether whole-body heat stress without exercise triggers cardiovascular, hormonal, and extracellular protein responses of exercise.Design: Randomized controlled trial. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 31 publications
2
53
0
Order By: Relevance
“…Elevated levels of epinephrine and norepinephrine are observed after exercise in all exercise conditions with greater increases in hot environments (17). This study corroborates that epinephrine and norepinephrine increase during exercise, more so in the heat than at RT and cold environment.…”
Section: Discussionsupporting
confidence: 77%
“…Elevated levels of epinephrine and norepinephrine are observed after exercise in all exercise conditions with greater increases in hot environments (17). This study corroborates that epinephrine and norepinephrine increase during exercise, more so in the heat than at RT and cold environment.…”
Section: Discussionsupporting
confidence: 77%
“…Whitham et al (2006) demonstrated increased eHsp72 was associated with higher plasma levels of catecholamines and heart rate, whilst it has also been observed that following passive heating, neither epinephrine nor norepinephrine was solely responsible for eHsp72 release (Whitham et al 2007). Johnson and Fleshner (2006) identified α-adrenergic stimulation, notably through norepinephrine elevation (Nielsen et al 1997;Ortega et al 2006;Whitham et al 2006;Giraldo et al 2010;Iguchi et al 2012) as responsible for Hsp72 release into the circulation, this alongside the work of Whitham et al (2006Whitham et al ( , 2007 suggest a requirement for individuals to be presented with sustained physiological challenge during exercise-heat stress (Johnson and Fleshner 2006). Exercise intensity, or α-adrenergic stimulation via norepinephrine is likely required to be above an intensity threshold to elicit significant eHsp72 response with the greater exercise intensity data from Périard et al (2012) leading to data contrasting that of Marshall et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise in hot and humid environments increases physiological strain on the body in comparison with temperate conditions (Galloway and Maughan 1997). Combined with exercise (exercise-heat stress), environmental manipulation to induce hyperthermia (Fehrenbach et al 2001;Oishi et al 2002;Moran et al 2006;Whitham et al 2007;Sandström et al 2008;Iguchi et al 2012) have been reported as stimuli for further increasing eHsp72 compared to exercise alone. Indeed a strong relationship exists between plasma eHsp72 and core temperature (Ruell et al 2006;Sandström et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as discussed above, whole body heat stress has been shown to trigger the release and recruitment of bone marrow-derived proangiogenic cells (49,66). Further, whole body heat stress evokes a marked increase in sympathoadrenal activity and an associated elevation in circulating levels of catecholamines (27). Catecholamines have been previously shown to contribute to skeletal muscle angiogenesis in a model of peripheral vascular insufficiency (7).…”
Section: Potential Mechanismsmentioning
confidence: 99%